Gender Factor-Impact on Employability: Special Reference to the Management Students in Kerala - Edmund Christopher, S; M. Pradeep, K (International Journal of Engineering and Technology, 2018)
Kerala is the State having height in Human development Index in the Country. It has got the highest literacy rate and also number one in female literacy. In case of employment Kerala is one among the last states of the country. Kerala the advantage is the state was declared as a state with 100% literacy. The women literacy rate is also higher in the state, People are having good economic and cultural back ground. Good at education and other economic aspects of life. Among the 3,34 crores of the people ( Census 2011) 1.6 crores are male and 1.74areÂ  female. If we take the percentage of literacy 96.11% men and 92.07% women are literate. The women in the state are strong enough to work in corporate culture. The problem generally faces in Kerala is there is not much of job opportunities in Kerala and hence employability. Women are equally a good work force in Kerala compared to men provided they should have opportunity to be given.Â